Concomitant Migraine and Temporomandibular Disorders are Associated With Higher Heat Pain Hyperalgesia and Cephalic Cutaneous Allodynia. Issue 10 (October 2016) - Chaves, Thais C.; Dach, Fabíola; Florencio, Lidiane L.; Carvalho, Gabriela F.; Gonçalves, Maria C.; Bigal, Marcelo E.; Speciali, José G.; Bevilaqua-Grossi, Débora
Abstract : Objectives: The aim of this study was to assess differences in the levels of hyperalgesia and cutaneous allodynia (CA) among women with migraine, temporomandibular disorders (TMD), or both. Materials and Methods: Eighty women participated in the study. Mean ages for the control group, TMD group, migraine group, and migraine+TMD group were 26.15 (95% confidence interval [CI], 28.73 to 23.57), 31.65 (95% CI, 37.82 to 25.48), 35.05 (95% CI, 40.37 to 29.73), and 34.20 (95% CI, 37.99 to 30.41) years, respectively. The 12-item Allodynia Symptom Checklist was administered to assess CA. All participants underwent the Quantitative Sensory Test to determine the cold-pain and heat-pain thresholds. Mechanical pain thresholds were assessed using Semmes-Weinstein monofilaments. One-way analysis of variance and χ 2 tests were used for statistical analysis. Alpha was set at 0.05 level for statistical significance. Results: For all sites evaluated, the mean cold-pain threshold values were significantly lower in the TMD, migraine, and TMD+migraine groups compared with the control group. However, the mean heat-pain threshold values in the extracephalic region were significantly smaller only for the TMD+migraine group compared with the control group (41.94°C; 95% CI, 40.54 to 43.34 vs. 44.79°C; 95% CI, 43.45 to 46.12; P =0.03). Mechanical hyperalgesia in orofacial and neck sites was significantly lower in the TMD and TMD+migraine groups compared with the control group. Mean total 12-item Allodynia Symptom Checklist score in the TMD+migraine group was significantly higher than in the migraine group (9.53; 95% CI, 7.45 to 11.60 vs. 6.95; 95% CI, 5.35 to 8.55; P =0.02). Conclusions: More pronounced levels of hyperalgesia and CA were found in patients with both TMD and migraine. Thus, it is suggested that the concomitant presence of TMD and migraine may be related to intensification of central sensitization.